Addressing challenges and solutions in teaching speaking skills to non-English course students at UTAR - Oon, Sammi Wei Ting (2025)
This study investigates the challenges and solutions in teaching speaking skills to non-English course students at Universiti Tunku Abdul Rahman (UTAR). Using a mixed-method approach, data were collected from 36 lecturers from the Faculty of Arts and Social Science (FAS) and the Centre for Extension Education (CEE) in Kampar campus. The research aimed to address two key questions which are the difficulties lecturers face in teaching speaking skills and the strategies they propose to improve students’ oral proficiency. Findings revealed that psychological barriers such as anxiety, low confidence, and fear of making mistakes, as well as linguistic difficulties such as limited vocabulary, weak sentence structure, pronunciation issues, and dependent on mother tongue usage were a major challenge to students’ speaking development. These results align with the existing literature and highlight the impact of both affective and linguistic factors on oral performance. The study also identified several effective strategies, such as role plays, language games, trial-and-error approaches, reading aloud, and the integration of technology were widely endorsed by lecturers. Additionally, creating a safe and supportive classroom environment and tailoring speaking tasks to students’ academic backgrounds were emphasized as crucial for enhancing participation and confidence. The implications of these findings highlights the importance of adopting interactive, learner-centered teaching methods and providing institutional support for language lecturers. While the study contributes valuable insights, its scope is limited by the sample size, location, and cross-sectional design. Recommendations for future research include expanding the sample across faculties and institutions, conducting longitudinal studies, and incorporating student perspectives to complement lecturers’ views. In conclusion, this study highlights the importance of psychological and linguistic difficulties in shaping speaking performance among non-English course students and provides practical strategies to address these challenges. The results contribute to a better understanding of how empathetic, adaptive, and technology-enhanced teaching approaches can foster more effective and engaging speaking lessons in ESL contexts.